2022
DOI: 10.1021/acs.joc.2c00690
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to Arylated and Allylated Cyclopropanes via Brønsted Acid-Catalyzed Dehydrative Coupling of Cyclopropylcarbinols

Abstract: A regioselective protocol for the synthesis of cyclopropyl derivatives that relies on Brookhart acid-catalyzed dehydrative coupling over substituted cyclopropylcarbinols without rearrangement is reported herein. The reactions proceed promptly at 25 °C with only 2.0 mol % catalyst loading and produce the cyclopropyl derivatives in excellent yields. This method is well tolerated with a vast range of cyclopropylcarbinols including aliphatic cyclopropylcarbinols, where no elimination product was obtained, demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Similar delocalization phenomenon of alkenes after oxidation has been reported previously . This is followed by a Friedel-Craft type alkylation from phenol 1 leading to a benzylic radical intermediate III . Pathway B commences with the oxidation of phenol ( 1a , E 1/2 = 1.70 V vs SCE in MeCN), forming radical species II followed by a strain-release event with BCB 2 .…”
Section: Resultssupporting
confidence: 80%
“…Similar delocalization phenomenon of alkenes after oxidation has been reported previously . This is followed by a Friedel-Craft type alkylation from phenol 1 leading to a benzylic radical intermediate III . Pathway B commences with the oxidation of phenol ( 1a , E 1/2 = 1.70 V vs SCE in MeCN), forming radical species II followed by a strain-release event with BCB 2 .…”
Section: Resultssupporting
confidence: 80%
“…In 2022, the Hazra group developed a regioselective synthetic methodology to afford cyclopropyl derivatives that relies on the Brookhart acid catalyzed dehydrative FC reaction of substituted cyclopropyl alcohols without rearrangement (Scheme 8 A). 59 This strategy was successful with a variety of cyclopropylcarbinols in excellent yields (up to 97%), including aliphatic cyclopropyl carbinols where no elimination product was observed. Various control experiments and Hammett correlation studies suggested involvement of a cyclopropylcarbinyl cation as a key intermediate followed by nucleophile addition.…”
Section: Alcohols As Alkylating Agentsmentioning
confidence: 98%
“…Based on the above results and precedent, [7] we proposed a plausible reaction mechanism of in situ generated Brookhart's acid catalysed N-alkylation of arylamines/heterocyclic amines for the synthesis of cyclopropyl derivatives and homoallyl amines (Scheme 6). Initially, the Brookhart's acid interacted with the nitrogen of amines and produced the anilinium-borate salt I.…”
Section: Chemistry-a European Journalmentioning
confidence: 96%
“…[6] The cyclopropylcarbinol rearrangement is an excellent example of using intrinsic ring strain to produce ring expansion and ring opening product. It proceeds with the formation of a presumed cyclopropylcarbinyl cation, [7] followed by either bond migration (ring expansion) to the cyclobutyl cation [8] or ring opening to generate a homoallyl cation. [9] These intermediates could easily be captured by various nucleophiles to provide more functionalized products.…”
Section: Introductionmentioning
confidence: 99%